ANALISIS PEMASARAN TOMAT DI KELURAHAN PAU KECAMATAN LANGKE REMBONG KABUPATEN MANGGARAI - Gabriella Agnes Febriyanti Leven; Marthen Robinson Pellokila; Paulus Un (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
This study aims to (1) identify tomato marketing channels in Pau Village, Langke Rembong District, Manggarai Regency, (2) analyze the marketing margins in each marketing channel, and (3) measure the level of tomato marketing efficiency. The study was conducted using a purposive location determination method. Respondents consisted of farmers, collectors, and retailers. The farmer sample was determined using a census method, while the trader livelihood was determined using a snowball sampling method. The data used included primary data obtained through observation, interviews, and questionnaires, as well as secondary data from various related agencies. Data analysis was carried out descriptively qualitatively to describe the marketing channels, and quantitatively to calculate marketing margins and efficiency. The results of the study indicate that there are two marketing channel patterns, namely direct marketing channels (farmers → end consumers) and indirect marketing channels (farmers → collectors → retailers → end consumers). In marketing channel I, the marketing margin was Rp0/Kg in conditions without marketing costs, and Rp1,000/Kg in conditions with marketing costs. Meanwhile, in marketing channel II, the total marketing margin is IDR 5,000/kg, distributed between collectors and retailers. The efficiency analysis results indicate that both marketing channels are efficient, with efficiency values ​​ranging from 0 to 33%. However, relatively, marketing channel I is more efficient due to lower marketing costs than marketing channel II. Thus, direct marketing channels provide greater benefits for farmers by minimizing marketing costs, while indirect marketing channels still play a crucial role in expanding product distribution. Therefore, the selection of marketing channels requires consideration of cost efficiency and the ability to reach a wider market.